Review of social behaviors and cultural reproduction from the perspective of Bourdieu’s Theories practice and reproduction - Dadman, Enayatullah; Aminzai, Wafiullah; Moradi, Masoma (Priviet Social Sciences Journal, 2025)
This study provides a comprehensive review of social behaviors and cultural reproduction using Bourdieu’s theories of practice and reproduction. Social behaviors and cultural patterns are central to understanding the reproduction of societal structures, yet they often go unexplored regarding power dynamics and individual agency. Bourdieu’s concepts of "habitus," "capital," and "field" offer a nuanced framework for analyzing how cultural practices and social behaviors perpetuate inequalities across generations. This study aims to critically examine how Bourdieu’s theoretical constructs contribute to the reproduction of cultural and social norms, focusing on the mechanisms that sustain social order. Utilizing a qualitative methodology, this study reviews the existing literature and theoretical applications of Bourdieu’s work by drawing on case studies across diverse social contexts. The findings indicate that Bourdieu’s theories provide valuable insights into how social behaviors are shaped by both individual actions and systemic structures. The research highlights that cultural reproduction is not merely an individual process but is deeply embedded in social fields where power dynamics are continuously negotiated. This review not only enriches the understanding of social behaviors but also demonstrates the relevance of Bourdieu’s theories in contemporary social and cultural studies.